2018
DOI: 10.1159/000488941
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histologic Evaluation of the Hysterotomy Site and Fetal Membranes after Open Fetal Surgery for Fetal Spina Bifida Repair

Abstract: Introduction: Among the risks associated with open fetal surgery, myometrium and fetal membrane issues are vexing problems since they may lead to uterine dehiscence or preterm premature rupture of membranes resulting in uterine rupture or preterm birth or both. The aim of this study was to examine whether stapled and sutured hysterotomy scars demonstrate partial or complete healing. Methods: Hysterotomy sites after open fetal surgery were clinically evaluated in 36 women during Caesarean section, classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The degree of histological inflammation and fibrosis of the hysterotomy scar observed in this study was similar to that produced with the stapler in both ovine and human studies [9,16]. The fibrosis was moderate and multifocal as seen with use of the AutoSuture Premium Poly CS*-57 stapler in the ovine model [9].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The degree of histological inflammation and fibrosis of the hysterotomy scar observed in this study was similar to that produced with the stapler in both ovine and human studies [9,16]. The fibrosis was moderate and multifocal as seen with use of the AutoSuture Premium Poly CS*-57 stapler in the ovine model [9].…”
Section: Discussionsupporting
confidence: 74%
“…In this single animal, the fibrosis was more multifocal than the mild fibrosis that was largely limited to the region surrounding suture material in the ovine model [9]. Adhesions from adipose tissue on the serosa were visualized similarly to those seen with human stapled hysterotomy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unequivocal benefits of open fMMC repair, there are specific intervention‐related maternal and fetal risks. These include oligohydramnios, chorioamniotic membrane separation, prelabour premature rupture of membranes (PPROM) and uterine scar dehiscence or rupture 1,3–6 . The latter leading to preterm delivery and eventual prematurity associated pathologies and intraoperative or postoperative bleeding 1 .…”
Section: Introductionmentioning
confidence: 99%
“…These include oligohydramnios, chorioamniotic membrane separation, prelabour premature rupture of membranes (PPROM) and uterine scar dehiscence or rupture. 1,[3][4][5][6] The latter leading to preterm delivery and eventual prematurity associated pathologies and intraoperative or postoperative bleeding. 1 Therefore, parental counselling must highlight the delicate balance between potential outcome benefits and risks for mother and fetus following open fMMC repair.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal risks included approximately 6% risk of pulmonary edema (attributed to use of tocolytics), 9% risk of blood transfusion at delivery, and need for a caesarean section for all future pregnancies, irrespective of other obstetric indications 163. Other studies have also found evidence of myometrium scarring and substantial thinning or dehiscence of the hysterotomy after open MMC repair 172. Tocolytics have been used preoperatively and postoperatively to minimize the risk of preterm birth after open MMC repairs 173…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%